2017
DOI: 10.1002/stem.2619
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cell Microvesicles Attenuate Acute Lung Injury in Mice Partly Mediated by Ang-1 mRNA

Abstract: Microvesicles (MVs) derived from human mesenchymal stem cells (MSC MVs) were demonstrated to ameliorate inflammation in lungs. We have found their content of mRNA for keratinocyte growth factor was partly involved in their therapeutic effects. As MSC MVs also contained a substantial quantity of angiopoietin-1 (Ang-1) mRNA, which plays an essential role in vascular stabilization and resolving inflammation, we hypothesized that Ang-1 mRNA might similarly account for a part of their therapeutic effects. We downre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
122
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 158 publications
(130 citation statements)
references
References 40 publications
5
122
1
2
Order By: Relevance
“…Angiopoietin-1 is an angiogenic growth factor that promotes the generation of stable and functional vasculature. Previous studies have demonstrated that angiopoietin-1 plays a crucial role in MSC therapy for ALI/ARDS [39,40]. In this study, we did not detect the level of angiopoietin-1 in the iPSC-CM and MEF-CM.…”
Section: Discussioncontrasting
confidence: 85%
“…Angiopoietin-1 is an angiogenic growth factor that promotes the generation of stable and functional vasculature. Previous studies have demonstrated that angiopoietin-1 plays a crucial role in MSC therapy for ALI/ARDS [39,40]. In this study, we did not detect the level of angiopoietin-1 in the iPSC-CM and MEF-CM.…”
Section: Discussioncontrasting
confidence: 85%
“…We also previously found that the secretion of Ang1 by MSCs was critical in restoring fluid transport across primary culture of human alveolar epithelial type II cells . More recently, Tang et al found that Ang1 in MSC MV was important in reducing inflammation and pulmonary edema in LPS induced ALI in mice. In the current study, we found that Ang1 gene expression in cytomix‐injured HLMVEC was significantly increased at 6 and 12 hours and Ang1 protein secretion was significantly increased at 6 hours following MSC MV treatment.…”
Section: Discussionmentioning
confidence: 68%
“…Containing a panoply of chemokines, growth factors, mRNA, and microRNA with antiinflammatory, regenerative, and immunomodulatory functions, exosomes are the paracrine and endocrine mediators that confer bmMSCs with their healing properties, a fact that taken together with their superior safety profile, stability, and scalability, makes exosomes a tantalizing, practical, and yet unexplored treatment option for COVID-19 [15][16][17][18]. Multiple preclinical studies have shown favorable therapeutic effects of bone marrow-derived exosomes delivered intravenously in animal models of acute lung injury, ARDS, asthma, and other inflammatory diseases, with analyses revealing reduced alveolar inflammation, enhanced edema clearance, restoration of leaky epithelial membranes, and other sequelae of cytokine storm [19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%